Analysis of the Effect of the Agriculture and Tourism Sectors on Gross Regional Domestic Product (GRDP) in East Lombok Regency - Suhipami, Pina; Wahidin, Wahidin; Yhuda, I Dewa Ketut (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this study was to analyze the extent of the influence of the agricultural sector and the tourism sector, both partially and simultaneously, on Gross Regional Domestic Product (GRDP) in East Lombok Regency. By using a causalitative descriptive research method using multiple linear regression analysis approaches, the data used in this study are secondary data obtained from the Central Statistics Agency (BPS) from 2012-2022. The sample used consists of tourism ADHK GRDP for the tourism sector, agricultural ADHK GRDP for the agricultural sector and overall GRDP for GRDP indicators. The results of this study indicate that both the agricultural sector and tourism sector variables have a positive influence on GRDP in East Lombok Regency. With a t-count value for the agricultural sector of 7.008> 2.306 t-table and a t-count value for the tourism sector of 2.591> 2.306.